2021
DOI: 10.1186/s41021-021-00197-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of heterocyclic aromatic amines in colorectal cancer: the evidence from epidemiologic studies

Abstract: Since Dr. Sugimura’s discovery of heterocyclic aromatic amines (HAA) in broiled fish, many epidemiological studies have been conducted to investigate their role in human cancers, often focusing on colorectal cancer. The difficulty in measuring HAA exposure from meat and fish intake in these studies has resulted in inconsistent findings. Because studying individuals who may be particularly susceptible to the carcinogenic effects of HAA might facilitate the demonstration of a link with cancer, multiple studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…The HCAs are transformed into genotoxic metabolites after being consumed and absorbed [ 158 , 159 ]. Numerous studies have postulated HCA as an oncogenic agent for CRC due to the correlation between greater HCA levels and a higher risk of CRC [ 160 , 161 , 162 ]. According to reports, HCAs can cause oxidative base damage, strand breakage, microsatellite instability, frameshift mutations, and microsatellite instability [ 163 ].…”
Section: Obesity-associated Alterations In the Gut Microbiome That Ma...mentioning
confidence: 99%
“…The HCAs are transformed into genotoxic metabolites after being consumed and absorbed [ 158 , 159 ]. Numerous studies have postulated HCA as an oncogenic agent for CRC due to the correlation between greater HCA levels and a higher risk of CRC [ 160 , 161 , 162 ]. According to reports, HCAs can cause oxidative base damage, strand breakage, microsatellite instability, frameshift mutations, and microsatellite instability [ 163 ].…”
Section: Obesity-associated Alterations In the Gut Microbiome That Ma...mentioning
confidence: 99%
“…This reaction usually occurs when creatinine, carbohydrates and amino acids are heated at high temperatures [11,12]. The IARC has classified some HAs as Class 2A and 2B human carcinogens [13] Polymers 2023, 15, 3914 2 of 13 as they can generate DNA adducts and increase the risk of cancers, especially liver, colon and prostate cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA adducts formed by the HAAs can induce mutations that may initiate/promote carcinogenesis (Ho et al ., 2015, 2017). A large number of studies showed that HAAs increased the risk of diseases, such as colorectal cancer, bladder cancer, prostate cancer, gastric cancer, and breast cancer (Koda et al ., 2017; Le Marchand, 2021; Lumbreras et al ., 2008; Pence et al ., 1998; Rabstein et al ., 2010). Therefore, the HAA content in the daily diet has attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%